2019
DOI: 10.1016/j.ijscr.2019.02.025
|View full text |Cite
|
Sign up to set email alerts
|

Gallbladder volvulus: A case report and review of the literature

Abstract: Highlights Gallbladder volvulus (GV) is a rare disease with less than 400 cases reported in the English literature. Preoperative diagnosis is a major challenge with only 4 cases being diagnosed on radiology. Critical constellation of presenting symptoms and signs along with radiology can help in timely diagnosis of GV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0
19

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(56 citation statements)
references
References 6 publications
0
37
0
19
Order By: Relevance
“…In Japan, GV rates reached up to 8.1% and 11.6% in autopsy and surgical series, respectively (4). Overall, GV represents around 1 case per 350,000 hospital admissions (6)(7)(8). Due to a difficult diagnosis, its incidence and significance are likely underestimated.…”
Section: Epidemiologymentioning
confidence: 99%
“…In Japan, GV rates reached up to 8.1% and 11.6% in autopsy and surgical series, respectively (4). Overall, GV represents around 1 case per 350,000 hospital admissions (6)(7)(8). Due to a difficult diagnosis, its incidence and significance are likely underestimated.…”
Section: Epidemiologymentioning
confidence: 99%
“…[4] The mechanical events may be suddenly changing in body position, violent peristalsis of adjacent internal organs, and blunt injuries. Studies have shown that level elevation of cholecystokinin causing by gallbladder peristalsis after a fatty meal may conclude to gallbladder torsion [5]. This is due to a gallbladder without adhesion to the liver, concluding to the torsional movement.…”
Section: Discussionmentioning
confidence: 99%
“…Because this condition leads to obstruction of biliary drainage and blood flow, a delay in diagnosis and treatment can be life-threatening. There have been only five reported cases of preoperative diagnosis [ 12 ].…”
Section: Discussionmentioning
confidence: 99%